Retroperitoneal Approach for Ureteropelvic Junction Obstruction: Encouraging Preliminary Results With Robot-Assisted Laparoscopic Repair - Blanc, Thomas; Kohaut, Jules; Elie, Caroline; Clermidi, Pauline; Pio, Luca; Harte, Caroline; Brönnimann, Enrico; Botto, Nathalie; Rousseau, Véronique; Sonigo, Pascale; Vaessen, Christophe; Lottmann, Henri; et al. (Frontiers in Pediatrics, 2019)
Introduction stating the aim of the study Robot-assisted laparoscopic pyeloplasty (RALP) is gaining acceptance among pediatric urologists. Few studies have evaluated the retroperitoneal approach for RALP. We share our experience from the first 2 years of a multidisciplinary pediatric robotic program in our center. Patients (or Materials) and Methods We performed a retrospective analysis of prospectively collected data of children undergoing RALP for ureteropelvic junction obstruction (n=50). Diagnosis was confirmed by ultrasound and Tc-99m mercaptoacetyltriglycine renal scan or MRI; the same criteria were used to evaluate outcome. Surgical approach was chosen according to a specific algorithm. Transperitoneal approach (n= 13) was reserved for horseshoe kidney, ectopic kidney, and redo surgery. We analyzed the 37 cases performed by a lateral retroperitoneal approach. Dismembered pyeloplasty was done for all cases and anastomosis was performed using a running monofilament 6/0 absorbable suture. All were drained by double J stent. Patient data, operating room parameters and postoperative course were recorded. Results The median age was 7.9 years (5.1–13.8); the youngest was 2 years old. The median weight was 23 kg (17–41) with the smallest weighing 12.4 kg. Aberrant crossing vessels were present in 18 children. Median set-up time, from skin incision until the end of the 4-port insertion, was 33 min (29-48). Median surgeon’s console time was 151 min (136-182). No conversion to an open procedure was necessary. The postoperative course was free of complications, except urinary tract infection in 6 children. All but 4 patients were discharged on day one. Median follow-up was 9 months (5-13). Redo pyeloplasty was not required. Practical training of other colleagues was possible after 10 cases performed by the same surgeon. Conclusion These preliminary results suggest that retroperitoneal RALP in children is feasible, safe and effective. It is an excellent option with ideal anatomical exposure. Longer term results as well as continued practice will identify and overcome any challenges and enable surgical mastery of this procedure which is still evolving.